Pengukuran Tingkat Kebisingan Aliran Sungai Cinangneng-Bogor dengan Menggunakan Aplikasi Sound Level Meter - Rahman Sidik; Neng Nenden Mulyaningsih (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Noise pollution can come from noise generated by nature, one of which is noise from river flows. Therefore, the aim of this research was to determine whether the sound intensity level of the river flow is still below the threshold value or whether it has disturbed human hearing. The research method used was to measure the sound intensity level of the Cinangneng-Bogor river flow by using a sound level meter application. Measurement of the sound intensity level was carried out at 5 measurement points, namely in the middle of the river flow, on the river bank, at a distance of 5 m, 10 m and 15 m from the river bank to the land. Each measurement was carried out for 120 seconds. The results showed that the sound intensity level of the Cinangneng-Bogor river flow at several measurement points had different values, namely from the middle of the river to away from the river the values were 96.34 DbA, 92.31 DbA, 78.93 DbA, 76.58 DbA and 76.32 DbA. In conclusion, the further away from the noise source, the lower the noise level. The sound intensity in the middle and on the river bank was above the threshold value.